A report on primary tuberculosis of glans penis - rare presentation of a common disease - Suchana Marahatta (Our Dermatology Online, 2018)
Penile tuberculosis is an extremely rare form of genitourinary tract tuberculosis even in developing countries with higher tuberculosis prevalence. A 38-year-old married male without promiscuous behavior presented to dermatology outpatient department with a single, painful penile ulcer of 1.5×1cm size for last 2 years; which got mildly improved after on and off treatment from local practitioner, but without complete resolution. All workup in the line of sexually transmitted diseases were negative. Incisional biopsy revealed diffuse granuloma, however stain for AFB (TB) was negative. He also had positive mantoux test and raised ESR. On these bases, we started him on category I-anti tuberculosis therapy; which resulted into complete resolution of ulcer leaving behind fibrotic scar. Hence, in country like Nepal where the prevalence of tuberculosis is high, we should always suspect tuberculosis in case of non-healing chronic ulcers.